(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The purpose of the study is to A STUDY OF RELATIONSHIP BETWEEN JOB SATISFACTION AND ITS DIMENSIONS OF FIRST GRADE DEGREE COLLEGES OF HUBLI-DHARWAD CORPORATION AREA, The nature of present study is of descriptive survey. 50 First Grade Degree Colleges of Hubli Dharwad Corporation area of Karnataka State were selected for the study. The findings of the study concluded that whenever the infrastructure facilities, physical facilities, human resources increases it support to increase the job satisfaction of principals. Whenever the infrastructure facilities, physical facilities and human and material resources increases it support to increase the administrative behaviour of the principals.